Hyperosmolar diabetic ketoacidosis-- review of literature and the shifting paradigm in evaluation and management. Issue 6 (November 2021) - Brar, Preneet Cheema; Tell, Shoshana; Mehta, Shilpa; Franklin, Bonita
Abstract: Background: Hyperosmolar diabetic ketoacidosis (H-DKA), a distinct clinical entity, is the overlap of diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic state (HHS). Aim: We describe the clinical presentation, metabolic aberrations, and associated morbidity/mortality of these cases with H-DKA. We highlight the problem areas of medical care which require particular attention when caring for pediatric diabetes patients presenting with H-DKA. Methods: In our study we reviewed the literature back to 1963 and retrieved twenty-four cases meeting the criteria of H-DKA: glucose >600 mg/dL, pH < 7.3, bicarbonate <15 mEq/L, and serum osmolality >320 mOsm/kg, while adding three cases from our institution. Results: Average age of presentation of H-DKA was 10.2 years ± 4.5 years in females and 13.3 years ± 4 years in males, HbA1c was 13%. Biochemical parameters were consistent with severe dehydration: serum osmolality = 394.8±55 mOsm/kg, BUN = 48±22 mg/dL, creatinine = 2.81±1.03 mg/dL. Acute kidney injury, present in 12 cases, was the most frequent end-organ complication. Conclusion: Multi-organ involvement with AKI, rhabdomyolysis, pancreatitis, neurological and cardiac issues such as arrhythmias, are common in H-DKA. Aggressive fluid management, insulin therapy and supportive care can prevent acute and long term adverse outcomes in children and adolescents. Highlights: Hyperosmolar diabetic ketoacidosis is an overlap condition between diabetic ketoacidosis and hyperosmolar state. It is characterized by high serum osmolality >300 mOsm/L along with acidosis <15 mmol/L in a patient with hyperglycemia. Multi-organ involvement with AKI, rhabdomyolysis, pancreatitis, neurological and cardiac issues such as arrhythmias occur. Aggressive fluid management, insulin therapy and supportive care can prevent complications and even death.